Dosage suppressors of gpn2ts mutants and functional insights into the role of Gpn2 in budding yeast. - Le Wang; Pan Li; Pei Zeng; Debao Xie; Mengdi Gao; Lujie Ma; Aamir Sohail; Fanli Zeng (PLoS ONE)
Gpn2 is a highly conserved protein essential for the assembly of RNA polymerase II (RNAPII) in eukaryotic cells. Mutations in Gpn2, specifically Phe105Tyr and Leu164Pro, confer temperature sensitivity and significantly impair RNAPII assembly. Despite its crucial role, the complete range of Gpn2 functions remains to be elucidated. To further explore these functions, we conducted large-scale multicopy suppressor screening in budding yeast, aiming to identify genes whose overexpression could mitigate the growth defects of a temperature-sensitive gpn2 mutant (gpn2ts) at restrictive temperatures. We screened over 30,000 colonies harboring plasmids from a multicopy genetic library and identified 31 genes that rescued the growth defects of gpn2ts to various extents. Notably, we found that PAB1, CDC5, and RGS2 reduced the drug sensitivity of gpn2ts mutants. These findings lay a theoretical foundation for future studies on the function of Gpn2 in RNAPII assembly.